Improving health equity through sustained academic partnership: development of a maternal-fetal medicine fellowship training program in Western Kenya - David Nding'ori, MMed; Rachel F. Spitzer, MD, MPH; Julia Songok, MMed; Marie Buitendyk, MD, MSc; Pallavi Mishra, MMed; Wycliffe Kosgei, MMed; Bett Kipchumba, MMed; Mutindi Kakuti, MMed; Philip Tonui, MMed; Karen Fung-; Heidi Leftwich, DO; Adrian Gardner, MD, MPH; et al. (Elsevier, 2024)
Low- and middle-income countries are underresourced in subspecialist care. This study describes a unique maternal-fetal medicine clinical fellowship training program at Moi University School of Medicine and Moi Teaching and Referral Hospital in Eldoret, Western Kenya. The first of its kind in Eastern Africa, it has met with success in the retention of highly qualified practitioners providing complex pregnancy care to a population that has been heretofore underserved.